Designing persuasive technology to personalise learning activities in FuPla portal / Syarifah Adilah Mohamed Yusoff... [et al.] - Mohamed Yusoff, Syarifah Adilah; Wan Mohammad, Wan Anisha; Mohd Mydin, Azlina; Johan, Elly Johana (Unit Penulisan Dan Penerbitan JSKM, 2022)
Nowadays, learning portals are becoming one of the popular learning tools in this era of pandemic. The existing of this tool becomes an essential necessity in the growth of Online Distance Learning (ODL). Challenges during ODL are students’ engagement in the learning process. Interactive multimedia (CSC253) course involved theoretical terms which can drives students to lose their interest and focus in learning. The content consists of fundamental concept which require students to have high memorizing skills. Online teaching and learning tools are used to help students learning and engaging on online learning. Persuasive technology is used as crucial component for long terms engagement. This study has investigated the concept of persuasive and potential elements to be implemented for ODL and further developed the FuPla portal to incorporate elements of think, cooperate, involve and learn independently in a fun way. This portal is developed based on the gaming concept incorporating persuasive technology.